Pelatihan Mengiring Lagu untuk Meningkatkan Keterampilan Bermusik Mahasiswa PGSD Universitas Negeri Gorontalo - Nurmila Sari Djau (Universitas Syiah Kuala, 2022)
The implementation of PGSD student graduates is expected to be able to provide experience in various fields of study, art learning is no exception. In art learning in elementary school teachers are not only able to provide an experience of appreciation but also an experience of expression, where students can sing songs accompanied by music or play musical instruments together. However, based on observations, PGSD students, especially at Gorontalo State University, still lack musical knowledge and skills. This is the basis for implementing PKM. The purpose of the PKM is to provide experience and hone the abilities of UNG PGSD students to accompany songs. The implementation method used is the first coordination of implementation time, technical implementation, implementation of activities, and evaluation. The results of this activity are increasing the insight and knowledge of UNG PGSD students regarding scales and chords, and this activity hones students' abilities in singing songs using keyboard instruments. This activity is also expected to stimulate students and lecturers to always deepen their musical skills so they can develop learning materials